Nano and Microparticles as Potential Oral Vaccine Carriers and Adjuvants Against Infectious Diseases - Jazayeri, Seyed Davoud; Lim, Hui Xuan; Shameli, Kamyar; Yeap, Swee Keong; Poh, Chit Laa (Frontiers in Pharmacology, 2021)
Mucosal surfaces are the first site of infection for most infectious diseases and oral vaccination can provide protection as the first line of defense. Unlike systemic administration, oral immunization can stimulate cellular and humoral immune responses at both systemic and mucosal levels to induce broad-spectrum and long-lasting immunity. Therefore, to design a successful vaccine, it is essential to stimulate the mucosal as well as systemic immune responses. Successful oral vaccines need to overcome the harsh gastrointestinal environment such as the extremely low pH, proteolytic enzymes, bile salts as well as low permeability and the low immunogenicity of vaccines. In recent years, several delivery systems and adjuvants have been developed for improving oral vaccine delivery and immunogenicity. Formulation of vaccines with nanoparticles and microparticles have been shown to improve antigen stability, availability and adjuvanticity as well as immunostimulatory capacity, target delivery and specific release. This review discusses how NPs and MPs as oral carriers with adjuvant characteristics can be beneficial in oral vaccine development.